Assessment of an anti-ageing structured cosmetic formulation containing goji berry - Leite, Fernanda de Godoy (2019)
Based on previous studies, it has been found that goji berry (GB), popularly known as a ‘miracle fruit’, has excellent antioxidant potential and can be used in the treatment of skin disorders associated with ageing. This study aimed to incorporate GB into a structured cosmetic in order to optimise its penetration. Stability studies of the formulation, determination of the antioxidant activity of the extract and of the formulation, rheological measurements, SAXS, polarised light microscopy and bioadhesion analyses were performed. The results indicated the antioxidant activity of the extract, which can be incorporated into an emulsified cosmetic formulation. The emulsified formulation containing the extract remained stable, even after being submitted to thermal and luminous stresses for 30 days. In addition, rheological tests revealed that the addition of the GB soft extract reduced the viscosity of the formulation, increasing thixotropy and deformation. These systems were characterised by SAXS as a lamellar phase, which was confirmed by polarised light microscopy. These highly organised structures indicate their excellent stability. In vitro bioadhesion experiments revealed that these formulations exhibited skin adhesion strength statistically similar to commercial anti-ageing formulation. These results suggest that this formulation has excellent potential to be used as a topical treatment for ageing.